Režimi blaginje in vprašanje razvrščanja držav v skupine v razširjeni EU - Mandič, Srna (Družboslovne razprave, 2008)
The article gives an overview of the diverse ideas of 'welfare regimes', extending from simplified, supposedly universal notions to more thoughtful views, acknowledging the variety of welfare regime typologies and critically assessing their explanatory powers in different life domains. Reference is also made to some of their bases in original works by Esping-Anderson. The author maintains that contemporary notions of welfare regimes are based on either a deductive or an inductive approach. It is argued that in the case of 'post-socialist' societies the deductive approach, which is based on 'ideal-typical' definitions of welfare regimes, has a number of limitations and weaknesses, thus also encouraging the use of other, more simple analytical concepts, based on a more inductive approach.
Keywords: Država blaginje; Welfare state; Tipologija; Typology; Postsocialism; Postsocializem; Države Evropske unije; European Union countries; postsocialistične države; Evropska unija; European Union